Case Report: Hematopoietic stem cell transplantation in an adult patient with X-linked agammaglobulinemia and severe refractory enteropathy - López-León, Paula Teresa; Cabañero-Navalon, Marta Dafne; Garcia-Bustos, Victor; Giner, Francisco; Balastegui Martín, Héctor; Asensi Cantó, Pedro; Montoro Gómez, Juan; Seguí-Cotano, Olga; Argente Pla, María; Moral Moral, Pedro (Frontiers in Immunology, 2025)
X-linked agammaglobulinemia (XLA) is a rare primary immunodeficiency characterized by absent B cells and severe hypogammaglobulinemia. While lifelong immunoglobulin replacement therapy (IgRT) effectively prevents severe infections, it does not prevent chronic complications in a subset of patients with immune dysregulation. We report the case of a young adult with genetically confirmed XLA and severe, treatment-refractory enteropathy with persistent Campylobacter jejuni and norovirus infections, who underwent successful allogeneic hematopoietic stem cell transplantation (HSCT) after exhausting all therapeutic options. Post-transplant, the patient achieved complete resolution of chronic diarrhea, clearance of enteric pathogens, and sustained independence from parenteral nutrition, with significant improvement in nutritional status, bone density, and quality of life. This case represents one of the few documented adult XLA transplants and highlights HSCT as a feasible, safe, and potentially curative option in selected patients with severe non-hematologic complications. It underscores the need to consider HSCT earlier in the disease course, especially when organ damage is progressive and irreversible. Further studies are needed to clarify indications, timing, and cost-effectiveness of HSCT in XLA.